Inconsistent stoichiometry and growth responses of two coexisting dominant species to various N and P supplies in a supratidal wetland of the Yellow River Delta - Liu, Xiaoling; Wang, Guangmei; Zhang, Haibo; Han, Guangxuan; Li, Kexin; Wang, Andong (Frontiers in Marine Science, 2023)
The availability and stoichiometry ratio of nitrogen (N) and phosphorus (P) play vital roles in plant trophic dynamics and primary production. However, the responses of these plant traits to varying N and P supplies remain largely unclear for supratidal wetland herbs. Here, we conducted a 4-year field manipulation experiment in a supratidal wetland in the Yellow River Delta. The changes in aboveground biomass, leaf N and P concentrations and N:P ratios of two dominant herbs (Suaeda glauca and Phragmites australis) were examined at 3 overall nutrient supply levels (low, medium and high) combined with 3 N:P supply ratios (5:1, 15:1 and 45:1). The results showed that the leaf trophic dynamics of the two dominant species rely on the overall supply level as well as on the N:P supply ratio, while the aboveground biomass of both species was only significantly influenced by the overall supply level. With the increase in supply level, S. glauca gained an advantage over P. australis in aboveground biomass competition. The leaf N and P concentrations of both species raised with the respective increasing nutrient inputs, and N:P improved with the increasing supply ratio. The leaf stoichiometry of S. glauca was more strongly influenced by the various N and P supplies than that of P. australis. Specifically, the gap of nutrient contents between the two species widened as nutrient availability improved, with the dominance of S. glauca increasing while that of P. australis decreasing. This species-specific response may explain the altered aboveground biomass of the two species. Our findings suggested that changing the N and P supply can potentially influence primary productivity by changing leaf nutrient status, indirectly affecting the shifts in plant dominance and community composition in supratidal wetland ecosystems.